Pulmonary endarterectomy in chronic thromboembolic pulmonary hypertension - YILDIZELİ, BEDRETTİN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2013)
Background: This study aims to assess the early results of pulmonary endarterectomy. Methods: Between March 2011 and July 2012, 64 patients (29 males, 35 females; mean age 47.4 +/- 10.4 years; range 14 to 78 years) who underwent pulmonary endarterectomy were retrospectively analyzed. Preoperative and postoperative Doppler echocardiographic evaluation of pulmonary arterial hemodynamics and right ventricular function were evaluated. Variables were expressed in a mean +/- standard deviation. The comparisons were made using independent sample t-test (p<0.05). A p value of <0.05 was considered significant. Results: The preoperative mean systolic pulmonary artery pressure was 75.4 +/- 25.5 mmHg, while the mean pulmonary vascular resistance was 801.7 +/- 449.5 dynes.sec.cm(-5). The postoperative mean systolic pulmonary artery pressure was 44.4 +/- 15.6 mmHg, whereas the mean pulmonary vascular resistance was 371.6 +/- 237.9 dynes.sec.cm(-5) (p<0.001 and p<0.001). Early mortality was seen in 10 patients (15.6%). Conclusion: Pulmonary endarterectomy is effective and safe in the treatment of chronic thromboembolic pulmonary hypertension. Its usage should be extended with support of experienced centers in Turkey.
Keywords: Endarterectomy; pulmonary artery; pulmonary embolism; pulmonary hypertension; right ventricular dysfunction; DEEP-VEIN THROMBOSIS; THROMBOENDARTERECTOMY; EMBOLISM; OUTCOMES; ARTERY; EXPERIENCE